Social Networks, Drug Injectors’ Lives, and HIV/AIDS - Friedman, Samuel R.; Curtis, Richard; Neaigus, Alan; Jose, Benny (Aids Prevention and Mental Health, 2002)
Social Networks, Drug Injectors' Lives, and HIV/AIDS recognizes HIV as a socially structured disease - its transmission usually requires intimate contact between individuals - and shows how social networks shape high-risk behaviors and the spread of HIV. The authors recount the groundbreaking use of social network methods, ethnographic direct-observation techniques, and in-depth interviews in their study of a drug-using community in Brooklyn, New York. They provide a detailed documentary of the lives of community members. They describe drug-use, the affects of poverty and homelessness, the acquisition of money and drugs, and social relationships within the group. Social Networks, Drug Injectors' Lives, and HIV/AIDS shows that social networks and contexts are of crucial importance in understanding and fighting the AIDS epidemic. These findings should revitalize prevention efforts and reshape social policy